2008
DOI: 10.1021/op700171b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Crystal Chemistry, the Process Conditions for Crystallization and the Relative Structural Stability of Two Polymorphic Forms of NG-monomethyl-l-arginine Hydrochloride

Abstract: Crystal structures of two conformational polymorphs (FormA and Form D) of N G -monomethyl-L-arginine hydrochloride, a drug developed to treat septic shock, are presented. Form A is orthorhombic in a tetra-molecular unit cell and Form D is monoclinic in a bimolecular unit cell (space groups P2 1 2 1 2 1 and P2 1 , respectively). The two forms display differences in the conformation of the terminal N-methyl group, which is cis in Form D and trans in Form A. Structural energy calculations demonstrate that Form D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…2 Strong intra molecular strength contributes to a good output in SHG, 9b which attracts a great deal of attention due to their large optical nonlinearities. 15 Recently, it has been observed that among many organic compounds reported for their second harmonic generation, chalcone derivatives have displayed excellent blue light transmittance, large first order hyperpolarizability with high damage threshold and good crystallizability. 13 Among the many known organic NLO materials, some chalcone materials exhibited extremely high and fast nonlinearity 1,2,16,17 and established a preference to crystallize in non-centrosymmetric structures.…”
Section: Introductionmentioning
confidence: 99%
“…2 Strong intra molecular strength contributes to a good output in SHG, 9b which attracts a great deal of attention due to their large optical nonlinearities. 15 Recently, it has been observed that among many organic compounds reported for their second harmonic generation, chalcone derivatives have displayed excellent blue light transmittance, large first order hyperpolarizability with high damage threshold and good crystallizability. 13 Among the many known organic NLO materials, some chalcone materials exhibited extremely high and fast nonlinearity 1,2,16,17 and established a preference to crystallize in non-centrosymmetric structures.…”
Section: Introductionmentioning
confidence: 99%